Clinical and electromyographic follow-up of myofascial pain patients treated with two types of oral splint: a randomized controlled pilot study = Klinische und elektromyografische Verlaufsuntersuchung von Patienten mit myofaszialen Schmerzen unter Therapie mit zwei unterschiedlichen Arten von Okklusionsschienen : eine randomisierte, kontrollierte Pilotstudie - Weggen, Tjerk; Schindler, Hans J.; Kordaß, Bernd; Hugger, Alfons (International journal of computerized dentistry, 2013)
Increased resting electromyographic activity (EMG), reduced EMG during maximum voluntary clenching, and a shift to lower frequencies of the mean/median power frequency (MPF) of the EMG power spectrum have been reported for patients with temporomandibular disorder pain. It is unclear, however, whether these electrophysiological phenomena can be correlated with symptom improvement during the follow-up of myofascial pain patients in treatment. The objective of this study was to monitor the therapeutic effects of two different splint concepts (standard method and a complex splint procedure assisted by transcutaneous electrical nerve stimulation, TENS) for a period of 12 weeks, by use of clinical outcome criteria and EMG recordings. We tested the hypotheses that both measures evaluated will change in parallel during treatment and that the different splint concepts will result in no outcome differences between the variables studied. For two randomly selected groups, each containing 20 non-chronic myofascial pain patients, the clinical course after splint insertion was documented over a period of 12 weeks on the basis of pain and pain on palpation ratings, in parallel with EMG recording. Baseline values were monitored for matched healthy subjects. Although there was no correlation between the course of symptom improvement and significant changes in EMG data, MPF differed significantly (p < 0.05) between healthy subjects and patients. The therapeutic effects of splints of different clinical complexity differed significantly (p < 0.05) between the patient groups, in favor of the complex oral appliances, and substantial (p < 0.001) but temporary pain relief was achieved by additional TENS. For non-chronic myofascial TMD pain patients treated with splints, the course of symptom improvement is not paralleled by significant changes in EMG data. MPF can, however, be used to distinguish between healthy subjects and patients. Splints of different clinical complexity differ in their therapeutic effects in non-chronic myofascial TMD patients, and substantial temporarily limited pain relief can be achieved by additional muscle stimulation by TENS.